Xanthogranulomatous Pituitary Adenoma in a Dog with Typical Hyperadrenocorticism. (October 2020) - Fernández-Gallego, Ana; Del-Pozo, Jorge; Boag, Alisdair; Maxwell, Scott; Pérez-Acino, Jorge
Summary: Xanthogranuloma of the sellar region has been reported in both humans and animals. The lesion is rare, and its aetiology and pathogenesis are not fully understood. The association of sellar xanthogranuloma with an adenoma, known as xanthogranulomatous pituitary adenoma (XPA), is an extremely rare condition in humans and is usually associated with anterior pituitary insufficiencies, headache, vomiting and visual deficits. We present the first report of XPA in an animal. A 7-year-old male neutered Labrador Retriever was presented for investigation of progressive lethargy, vomiting and hyporexia, having been previously diagnosed with chronic kidney disease, pituitary-dependent hyperadrenocorticism and hypoparathyroidism. The dog was euthanized due to lack of response to medical treatment and post-mortem examination revealed XPA. Although rare, xanthogranulomatous lesions should be considered in patients with pituitary disease.